2016
DOI: 10.1177/0885328216633374
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the in vitro photocatalytic antibacterial activity of nanocrystalline TiO2 and coupled TiO2/Ag containing copolymer on the surface of medical grade titanium

Abstract: Antibacterial surfaces have been in the focus of research for years, driven by an unmet clinical need to manage an increasing incidence of implant-associated infections. The use of silver has become a topic of interest because of its proven broad-spectrum antibacterial activity and track record as a coating agent of soft tissue implants and catheters. However, for the time being, the translation of these technological achievements for the improvement of the antibacterial property of hard tissue titanium (Ti) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 34 publications
0
28
0
Order By: Relevance
“…Silver has been known as a broad-spectrum bactericide for centuries. It has been demonstrated that silver nanoparticle coatings on Ti based implants increased their biocompatibility and antibacterial properties (Gyorgyey et al 2016;Sulej-Chojnacka et al 2016). Titanium dioxide (TiO 2 ) has also been known as a broad-spectrum bactericide for a long time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Silver has been known as a broad-spectrum bactericide for centuries. It has been demonstrated that silver nanoparticle coatings on Ti based implants increased their biocompatibility and antibacterial properties (Gyorgyey et al 2016;Sulej-Chojnacka et al 2016). Titanium dioxide (TiO 2 ) has also been known as a broad-spectrum bactericide for a long time.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, TiO 2 with moderate hardness and excellent resistance to wear and corrosion can significantly accelerate osteoblast cell growth and improve bone-forming functionality and direct the fate of stem cells in orthopedic-associated implants (Frandsen et al 2013;. This suggests that a Ag-TiO 2 nanocomposite coating may offer a promising solution for improvement of the antibacterial properties of dental and orthopedic implants (Cotolan et al 2016;Gyorgyey et al 2016). It has been reported that Ag-TiO 2 nanocomposite coatings exhibit a synergistic effect on antibacterial activity, which made their bactericidal activities stronger than Ag or TiO 2 coatings (Ashkarran et al 2011;Esfandiari et al 2014;Motlagh et al 2014;Prakash et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Two photocatalytic layers: 60 % TiO 2 / 40 % copolymer and 60% AgTiO 2 / 40 % copolymer ([Ag] = 0.001 m/m %) were investigated. We reduced the amount of nanosilver from 0.5 % to 0.001% compared to our previous experiments 26 . A hydrophilic polyacrylate resin [poly (ethyl-acrylate comethyl-methacrylate) (p(EA-co-MMA)) binder material (obtained from Evonik Industries, Germany) was used providing the polymer bed for TiO 2 and Ag photocatalyst nanoparticles.…”
Section: Preparation Of Ag-tio 2 Copolymer Filmsmentioning
confidence: 99%
“…The oral microbiota is a very complex ecological community that hard to model exactly, since it contains a huge number of culturable and unculturable bacteria which need special demands to their viability and proliferation [15,16]. Our research group previously used Streptococcus strain as a model organism for dental research [17]. Therefore, in this study we also applied a simplified in vitro model and chose pioneer colonizers (Streptococcus mitis, Streptococcus salivarius) to our investigations.…”
Section: Introductionmentioning
confidence: 99%